A computation-driven, energy-efficient and hybrid of microwave and conventional drying process for fast gooseberry candy production. Issue 4 (2nd October 2019) - Singh, Chanpreet; Saluja, Nitin; Sharma, Rajeev Kamal
Abstract: The health benefits of Indian gooseberry have resulted in a tremendous growth in its consumption in the form of tasty candy and marmalade prepared by drying process. The candy production process is limited by high drying time and plant size requirements as most of the processing production plants are equipped with conventional drying methods. Hence, the paper presents computational model defining relation between electric field pattern with heating and moisture diffusion in the product simultaneously. The boundary value applies on Maxwell's equation solution as defined by gooseberry electrical properties. The solution to heat and mass transfer equation offers thermodynamic properties and profiles of gooseberry by microwave heating. The optimised process of moisture diffusion to the surface of gooseberry, followed by conventional heating, dries the sample uniformly and speeds up the process. The established relation offers a valid model for defining time for microwave and conventional heating of fresh gooseberry that takes it as an input and dries gooseberry candy as an output, thereby reducing the time of drying from 17 hours to 0.5 hour. The electromagnetic and thermodynamic results are obtained using simulation and are followed by experimental verification.